The origins and provisional nature of Iceland's 1944 constitution - Guðni Th. Jóhannesson (Icelandic Review of Politics & Administration, 2011)
The article looks at the origins of the 1944 constitution of Iceland, when the country declared its full independence from Denmark. It focuses on the years of the Second World War and places special emphasis on the constraints which members of parliament imposed on themselves in changing the constitution. Primarily, the leaders of the political parties in parliament were convinced that unless they agreed to change the constitution as little as possible,fierce quarrels would arise within parliament and amongst the public. That, however, had to be avoided since it was of vital importance that the outside world would see a nation united in its desire for full independence. Consequently, most MPs and others involved in the writing of the new constitution agreed that it would be a temporary measure. As soon as it had been ratified, however, work could begin on its revision. The conclusion is that in later debates in Iceland about the constitution, this crucial element has sometimes been overlooked or downplayed.